Process of Development of WHO Guidelines - Bellad, Asha; Gupta, Aakriti (Indian Journal of Community Health, 2018)
A WHO guideline is any document containing recommendations about health interventions, whether these are clinical, public health or policy recommendations. A recommendation provides information about what policy-makers, health-care providers or patients should do. It implies a choice between different interventions that have an impact on health and that have implications for the use of resources. The purpose of WHO guidelines is to improve the health and well-being of individuals and populations